Immune responses in COVID-19 and tuberculosis coinfection: A scoping review - Kevin Flores-Lovon; Kevin Flores-Lovon; Brando Ortiz-Saavedra; Brando Ortiz-Saavedra; Luis A. Cueva-Chicaña; Luis A. Cueva-Chicaña; Shalom Aperrigue-Lira; Shalom Aperrigue-Lira; Elizbet S. Montes-Madariaga; Elizbet S. Montes-Madariaga; David R. Soriano-Moreno; Brett Bell; et al. (Frontiers in Immunology, 2022)
Background and aimPatients with COVID-19 and tuberculosis coinfection are at an increased risk of severe disease and death. We therefore sought to evaluate the current evidence which assessed the immune response in COVID-19 and tuberculosis coinfectionMethodsWe searched Pubmed/MEDLINE, EMBASE, Scopus, and Web of Science to identify articles published between 2020 and 2021. We included observational studies evaluating the immune response in patients with tuberculosis and COVID-19 compared to patients with COVID-19 alone.ResultsFour cross-sectional studies (372 participants) were identified. In patients with asymptomatic COVID-19 and latent tuberculosis (LTBI), increased cytokines, chemokines, growth factors and humoral responses were found. In addition, patients with symptomatic COVID-19 and LTBI had higher leukocytes counts and less inflammation. Regarding patients with COVID-19 and active tuberculosis (aTB), they exhibited decreased total lymphocyte counts, CD4 T cells specific against SARS-CoV-2 and responsiveness to SARS-CoV-2 antigens compared to patients with only COVID-19.ConclusionAlthough the evidence is limited, an apparent positive immunomodulation is observed in patients with COVID-19 and LTBI. On the other hand, patients with COVID-19 and aTB present a dysregulated immune response. Longitudinal studies are needed to confirm these findings and expand knowledge.